2021
DOI: 10.29313/gmhc.v9i3.8337
|View full text |Cite
|
Sign up to set email alerts
|

Level of Depression, Anxiety, and Stress of College Students in Indonesia during the Pandemic COVID-19

Abstract: The COVID-19 pandemic has caused a shift in learning methods to online. The obstacles felt by college students can have an impact on mental health. However, data on student mental health in Indonesia during the pandemic is still limited. This study describes the depression, anxiety, and stress of college students in Indonesia during the COVID-19 pandemic. This research method is descriptive, conducted on college students in Indonesia from July to August 2021. Sampling is done by voluntary sampling collection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It is unavoidable that even though students demonstrated adequate levels of selfregulated learning, most participants reported that they have experienced stress (92.1%) related to online learning, particularly in the first 0 to 7 months of online learning (65.4%). Besides that, the previous research found that mental health problems commonly happen at 17-29 years old (Beiter et al, 2015;Fauziyyah et al, 2021;Romadhona et al, 2021), whereas participants in this research aged 19-21 years old. Each individual has self-regulated learning, which results in different responses to changes in learning and instructions; some students would have difficulty concentrating or exert great effort in the new learning environment selfadjustment (Li et al, 2021;Schunk & Greene, 2018).…”
Section: Discussionmentioning
confidence: 62%
“…It is unavoidable that even though students demonstrated adequate levels of selfregulated learning, most participants reported that they have experienced stress (92.1%) related to online learning, particularly in the first 0 to 7 months of online learning (65.4%). Besides that, the previous research found that mental health problems commonly happen at 17-29 years old (Beiter et al, 2015;Fauziyyah et al, 2021;Romadhona et al, 2021), whereas participants in this research aged 19-21 years old. Each individual has self-regulated learning, which results in different responses to changes in learning and instructions; some students would have difficulty concentrating or exert great effort in the new learning environment selfadjustment (Li et al, 2021;Schunk & Greene, 2018).…”
Section: Discussionmentioning
confidence: 62%
“…A study assessing the level of depression, anxiety, and stress of college students in Indonesia during the Covid-19 pandemic concluded that the majority of college students suffer from moderate depression, severe anxiety, and severe stress. 20 Especially in the Covid-19 pandemic situation, the female students tent to perceive higher stress due to some pressures because they were more likely to ruminate during stressful situations and had a lower sense of mastery over their lives, which could lead to emotional eating as their coping mechanism. 21 In this study, it is shown that PCS had a higher score than MCS.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this research, further research has been carried out [2] regarding the mental health of students at College and poor mental health by 41%. Other research [3] on a sample of 258 students in Indonesia between July and August 2021 showed that the majority of students experienced moderate depression (12.8%), very severe anxiety (20.9%), and severe stress (13.6%).…”
Section: Introductionmentioning
confidence: 95%
“…Based on research results [1], [2], and [3] it is known that mental health disorders in students are something that commonly occur without even the students themselves realizing it. Even though they know, students just keep quiet or, worse, make the wrong self-diagnoses about their mental health.…”
Section: Introductionmentioning
confidence: 99%